Why does the productivity of investment vary across countries? - Nell, Kevin S.; Thirlwall, A.P. (PSL Quarterly Review, 2017)
In ‘new growth theory’ equations that include the investment ratio, all other variables included are determinants of the productivity of investment. We convert a ‘new growth theory’ equation into a productivity of investment equation by dividing the equation through by the investment ratio. We take a sample of 84 developed and developing countries over the period 1980 to 2011, and examine the importance of 19 potential variables that might affect the productivity of investment, using a general-to-specific model selection algorithm. Education, export growth, macroeconomic stability, political rights, geography and government expenditure turn out to be the most important determinants. There is no evidence of diminishing returns to investment, so that investment matters for long run growth. JEL Classification: 011; 033; 047